Crystallisation of aspirin via simulated pulmonary surfactant monolayers and lung‐specific additives. (4th April 2017) - Davies, Michael J.; Taylor, Zoe; Leach, Andrew G.; Ren, James; Gibbons, Paul
Abstract : Pain is a prevalent condition that can have a serious impact upon the socioeconomic function of a population. Numerous methods exist to administer analgesic medication (e.g. aspirin) to the body however inherent drawbacks limit patient acceptability. The inhaled route offers promise to facilitate the administration of medication to the body. Here, we consider the crystallisation behaviour of aspirin, our model therapeutic agent, when in contact with material of relevance to the lung. Thus, our approach aims to better understand the interaction between drug substances and the respiratory tract. Langmuir monolayers composed of a mixed surfactant system were supported on an aqueous subphase containing aspirin (7.5 mg/ml). The surfactant film was compressed to either 5mN/m (i.e. inhalation end point) or 50 mN/m (i.e. exhalation end point), whilst located within a humid environment for 16 h. Standard cooling crystallisation procedures were employed to produce control samples. Antisolvent crystallisation in the presence or absence of lung‐specific additives was conducted. All samples were analysed via scanning electron microscopy and X‐ray diffraction. Drug‐surfactant interactions were confirmed via condensed Langmuir isotherms. Scanning electron microscopy analysis revealed plate‐like morphology. The crystallisation route dictated both the crystal habit and particle size distribution. Dominant reflections were the (100) and (200) aspects. The main modes of interaction were hydrogen bonding, hydrophobic associations, and van der Waals forces. Here, we have demonstrated the potential of antisolvent crystallisation with lung‐specific additives to achieve control over drug crystal morphology. The approach taken can be applied in respirable formulation engineering. Copyright © 2017 John Wiley & Sons, Ltd.